PENGUJIAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG OLEH MAHKAMAH KONSTITUSI - Imbawani, Djoko (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
Constitutional Court (MK) through Verdict Number 138/PUU-VII/2009 have, conclusionÂ that authoritative MK to check, toÂ judging, and breaking application of examination of Regulation of Government of Substitution of Code.Â ThoughÂ articleÂ 24Â CÂ sentenceÂ (1)Â Constitution ofÂ IndonesiaÂ StateÂ 1945Â (IIIÂ amendment)Â forÂ example authoritative testÂ inviter codeÂ toÂ constitution,Â to uphold supremacy of constitution. AssessmentÂ toÂ regulation ofÂ government ofÂ substitutionÂ ofÂ codeÂ accordingÂ toÂ ruleÂ articlesÂ 22Â sentenceÂ (2) Constitution ofÂ Indonesia StateÂ 1945Â conductedÂ byÂ ParliamentÂ inÂ nextÂ conference.ThisÂ ResearchÂ typeÂ isÂ researchÂ ofÂ lawÂ ofÂ normative. Approach which utilized in this research is approach of law philosophy, approach of law theory, and constitutional approach. The system based on the Constitutionâs attempt to RIS or UUDS,Â judicial it does not allow review of productÂ in theÂ form ofÂ legislative act becauseÂ the productÂ is aÂ result of the exercise ofÂ sovereignty,Â let alone judicialÂ reviewÂ againstÂ a Perpu.Â Similarly a Perpu born based onÂ the ConstitutionÂ of 1945Â (originalÂ text) also cannot be doneÂ yudicialÂ review. After he didÂ theÂ amendment toÂ the Constitution process yudicial reviewÂ can be done. Yudicial review against a Perpu can be done, butÂ the need for the restriction that a Perpu substance shouldÂ setÂ things outsideÂ theÂ realm ofÂ theÂ Executive branchÂ can doÂ yudicial review.